Comparison of pKa values for oxy-enzymase derivatives derived from 3-acetyl and 4-acetyl-3 serotonin by using glass pole - Adel Azzoz; rawaa Suliaman (College of Education for Pure Sciences, 2014)
The study includes the preparation of four syn and anti oximes derived from mother ketones, namely 3-acetyl and 4-acetyl pyridine by standard method. The structures of these oximes were confirmed by using UV and IR spectra, melting points and specific chemical tests. The main aim of the study was the determination of pKa for these prepared oximes by potentiometric titration method, which was found, simple, fast and accurate. Finally, the study concluded that values of ionization constants depend on three main factors as:- The structure of oxime. Type of syn and anti isomer. Temperature.